ChemInform Abstract: Copper‐Catalyzed Reaction of Trifluoromethylketones with Aldehydes via a Copper Difluoroenolate. Issue 20 (April 2016) - Doi, Ryohei; Ohashi, Masato; Ogoshi, Sensuke
Abstract: The use of Bpin2 as the reductant, NaOtBu as base, and CuCl/phen as catalyst system permits an interesting defluorinative coupling of trifluoromethylketones with aldehydes to give moderate to good yields of α, α‐difluoro‐β‐hydroxyketones.